Subclinical Hypothyroidism in Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis - Ding, Xiaohong; Yang, Lili; Wang, Jian; Tang, Rong; Chen, Qianqian; Pan, Jiexue; Yang, Haiyan; Chen, Xia; Chen, Zimiao; Mu, Liangshan (Frontiers in Endocrinology, 2018)
Background: The association between subclinical hypothyroidism (SCH) and polycystic ovary syndrome (PCOS) has been reported in several studies，but it is not well recognized. The aim of this study was to evaluate the prevalence of SCH in women with PCOS. Methods: An extensive literature search was conducted in PubMed, Embase, Web of Science, and Cochrane Library databases. All articles published before May 2018 was considered for eligibility. No language restrictions were implemented. The prevalence of SCH in PCOS was performed by the meta-analysis to produce an odds ratio (OR) with 95% confidence interval (CI). Results: A total of 6 studies including 692 PCOS patients and 540 controls were eligible for the meta-analysis. The combined odds ratio (OR) of SCH risk for women with PCOS compared with controls was 2.87 (95% CI=1.82-9.92; P <0.000001). The OR increased to 3.59 when limiting TSH cut-off. Conclusions: This meta-analysis demonstrated that women with PCOS were more likely to develop SCH.